Resurrection Preaching in the Gospel of John - Lewis, Karoline M. (Religions, 2024)
The Gospel of John, without having its own liturgical year, is typically assumed to have a supplemental homiletical role in the Revised Common Lectionary, and yet the Fourth Gospel is the designated Gospel reading for the festival Sundays of Christmas, Easter, Pentecost, and Easter season. As a result, the theological themes of the Fourth Gospel anchor the church’s Trinitarian confessions and doctrinal imagination when it comes to preaching. In particular, as the assigned Gospel for the Sundays of Easter, the Gospel of John shapes resurrection proclamation. Resurrection proclamation, therefore, is animated by Jesus’ final words to his disciples found in the Farewell Discourse (John 14–17), where Jesus interprets his own ministry, commissions his disciples, testifies to the Paraclete, and prays for his followers. This essay will explore how the viewpoint of Jesus’ departing declarations makes a difference for preaching the resurrection. Through the lens of the Farewell Discourse, the promise of the resurrection takes on thematic issues that give important meaning to Jesus’ own revelation, “I am the resurrection and the life”.